The female of Xysticus pseudorectilineus (Wunderlich, 1995) (Araneae: Thomisidae) from Turkey - Demir, Hakan; Aktas, Metin; Seyyar, Osman (Zootaxa, 2008)
The genus Xysticus C. L. Koch, 1835 is represented by many taxa (156 species and 24 subspecies) in the Pale-arctic region (Platnick 2007). Xysticus pseudorectilineus, described by Wunderlich from Adana province (Kadirli district, Tuzla), is one of 36 species of this genus that have been recorded from Turkey (Topçu et al. 2005; Logunov & Demir 2006; Logunov 2006; Demir et al. 2006). This species was previously known only from a single male from the type locality (Wunderlich 1995). Xysticus pseudorectilineus is here redescribed based on 40 specimens of both sexes that were found in the different parts of Anatolia (Fig. 8). It has found to be common under stones. The male is adult in autumn, while adult females can be found in spring and autumn.